The AMIA Experience: Supporting local actions for Climate Resilient Agriculture - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Monville-Oro, Emilita; Gonsalves, Julian Francis; Ilaga, Alicia; Sebastian, Leocadio S.; Manalo, U-Nichols; Baltazar, Perla (International Institute for Rural Reconstruction, 2019)
The brief tackles how the Adaptation and Mitigation Initiative in Agriculture (AMIA) Program of the Philippines’ Department of Agriculture (DA) served as a platform for supporting local actions for climate resilient agriculture. The document discusses a number of key lessons emerging from the AMIA Village experience on the importance of local platforms for adaptation in the form of Climate-Smart Villages towards overall resilience building of the sector.